IMPLEMENTATION OF REMEDIAL, REPORTING AND UTILIZATION OF ASSESSMENT RESULTS IN THE INDEPENDENT CURRICULUM IN HIGH SCHOOL - Rafizal; Syarifah Rahmah; Jalaluddin; Nia Wardhani (RADJA PUBLIKA, 2025)
The implementation of the Independent Curriculum demands a paradigm shift in learning assessment, particularly in the implementation of remedial classes, reporting, and utilization of assessment results as a basis for learning improvement. However, at the senior high school level, the practice of these three aspects still faces various obstacles, both in terms of teacher understanding and the ongoing management of assessment results. This study aims to describe the implementation of remedial classes, reporting, and utilization of assessment results in the Independent Curriculum in senior high schools. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through learning observations, teacher interviews, and documentation studies of teaching materials and student learning outcomes reports. The results show that remedial classes have been implemented with adjustments to students' learning needs, although not yet fully based on in-depth mapping of learning outcomes. Reporting of assessment results has adhered to descriptive and informative principles, but is still limited in providing comprehensive feedback to students and parents. Furthermore, the use of assessment results as a basis for planning further learning has begun to be implemented, but is not yet consistent across all subjects. This study concludes that the implementation of remedial, reporting, and utilization of assessment results in the Independent Curriculum in Senior High Schools has been running, but still requires strengthening in the aspects of planning, consistency of implementation, and teachers' understanding of the function of assessment as a tool to improve the quality of learning.